Liver governs adipose remodelling via extracellular vesicles in response to lipid overload - Yue Zhao (Nature Portfolio, 2020)
Extracellular vesicles (EVs) containing miRNAs or proteins can coordinate metabolic responses between tissues. Here the authors demonstrate that during lipid overload, the liver secretes miRNA-containing EVs through a Ggpps-Rab27 dependent mechanism, which controls adipose tissue lipid storage capacity.